1-Acetyl-5-phenyl-1H-pyrrol-3-ylacetate: An aldose reductase inhibitor for the treatment of diabetic nephropathy. Issue 18 (15th September 2017) - Xiu, Zhi-Ming; Wang, Li-Ping; Fu, Jun; Xu, Jia; Liu, Li
Graphical abstract: Abstract: Diabetic nephropathy (DN) is the most common and serious complication in diabetes mellitus, but the efficacy of available strategies for preventing this disorder remains poor. The aim of this study was to investigate the possible beneficial effects of 1-acetyl-5-phenyl-1H-pyrrol-3-ylacetate (APPA), an aldose reductase inhibitor, on DN. In the present study, a model of rat glomerular mesangial cells (HBZY-1) damaged by high glucose was used to confirm the protective effects of APPA in vitro. Then, a rat model of streptozotocin-induced diabetes was used to assess the effects of APPA in vivo. APPA increased viability and reduced apoptosis in HBZY-1 cells. In vivo, APPA improved the signs of DN as determined by measurements of blood glucose, urinary microalbumin, serum total antioxidant capacity, serum catalase activity, serum glutathione levels, and serum total superoxide dismutase activity. Hematoxylin and eosin staining of kidney tissue confirmed the protective effect. Moreover, APPA reduced the levels of transforming growth factor-β1, collagen IV, and laminin in HBZY-1cells incubated in high glucose, and in serum in DN rats. In summary, APPA can effectively prevent apoptosis and the symptoms of streptozotocin-induced diabetes by inhibiting the polyol pathway in rats. This suggests that APPA could be a potential drug in treating DN.